2012
DOI: 10.1590/s0103-84782012000500026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the spontaneous fermentation and the ageing on the chemo-sensory quality of Brazilian organic cachaça

Abstract: This study verified the effect of the spontaneous fermentation/natural ferment (NF) on the chemo-sensory quality of cachaça, comparing to the commercial ferment (CF). The effect of ageing (maturation) was also analysed in the (pH, acidity, alcohol content, copper and secondary compounds) and sensory acceptability (aroma, flavour, colour, body and global impression RESUMO Este trabalho teve por objetivo avaliar o efeito da fermentação espontânea/fermento natural (NF) sobre a qualidade fisico-química e acei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
2
2
1
1
Order By: Relevance
“…Under the current Brazilian legislation, the addition of up to 6 g L -1 of sugars is allowed for sugarcane spirits and cane liquor (BRASIL, 2005). Table 3 shows the results of the analyses conducted by gas phase chromatography, which are consistent and close to those found by Gabriel et al (2012), on studying the influences of two types of yeast (natural and commercial) used as raw material for the production of their organic sugarcane drink. Figure 1 shows the chromatograms of Sample 11 (A) and the standards (B) of the alcohols and the ethyl acetate.…”
Section: Resultssupporting
confidence: 74%
“…Under the current Brazilian legislation, the addition of up to 6 g L -1 of sugars is allowed for sugarcane spirits and cane liquor (BRASIL, 2005). Table 3 shows the results of the analyses conducted by gas phase chromatography, which are consistent and close to those found by Gabriel et al (2012), on studying the influences of two types of yeast (natural and commercial) used as raw material for the production of their organic sugarcane drink. Figure 1 shows the chromatograms of Sample 11 (A) and the standards (B) of the alcohols and the ethyl acetate.…”
Section: Resultssupporting
confidence: 74%
“…However, there was a difference in copper concentration for the cachaça produced by the RB867515 variety, with the highest concentration detected in the cachaça from the organic management, which did differ from management without fertilization, but not from conventional management ( Table 1). The results presented in this research differ from those determined by Gabriel et al (2012), who found no differences in copper concentration in the cachaças produced with different cane varieties and types of fermentation under organic management, for example.…”
Section: Coppercontrasting
confidence: 99%
“…The low values of this element in cachaça corroborate those presented by Bortoletto and Alcarde (2015) and Gabriel et al (2012). Nevertheless, they are different from the values obtained by Fernandes et al (2007) and Pereira et al (2012), who determined copper concentration in cachaças and detected levels above that allowed by the legislation.…”
Section: Coppersupporting
confidence: 72%
“…In cachaça production, distillation separates ethanol from wine (hydroalcoholic solution). Wine distillation is based on three fundamentals: boiling point, affinity with alcohol or water, and alcoholic content during distillation (Gabriel et al, 2012).…”
Section: Distillationmentioning
confidence: 99%